Characterization of Nestin, a Selective Marker for Bone Marrow Derived Mesenchymal Stem Cells - Liang Xie; Xin Zeng; Jing Hu; Qianming Chen (Stem Cells International)
Mesenchymal stem cells (MSCs) are multipotent cells capable of differentiating into multiple cell lineages and contributing to tissue repair and regeneration. Characterization of the physiological function of MSCs has been largely hampered by lack of unique markers. Nestin, originally found in neuroepithelial stem cells, is an intermediate filament protein expressed in the early stages of development. Increasing studies have shown a particular association between Nestin and MSCs. Nestin could characterize a subset of bone marrow perivascular MSCs which contributed to bone development and closely contacted with hematopoietic stem cells (HSCs). Nestin expressing (Nes+) MSCs also play a role in the progression of various diseases. However, Nes+ cells were reported to participate in angiogenesis as MSCs or endothelial progenitor cells (EPCs) in several tissues and be a heterogeneous population comprising mesenchymal cells and endothelial cells in the developing bone marrow. In this review article, we will summarize the progress of the research on Nestin, particularly the function of Nes+ cells in bone marrow, and discuss the feasibility of using Nestin as a specific marker for MSCs.